HUBUNGAN KONSEP DIRI DENGAN KEJADIAN SCABIES DI PONDOK PESANTREN AL-QODIRI JEMBER - Prasetya, Fika Indah (MEDICAL JURNAL OF AL-QODIRI, 2019)
Health Development aims to improve health, the ability to live healthy to achieve optimal health degrees. Pesantren is one of formal and non formal education. Pesantren hasa solid activity, it needs special attention in the field of health in self-concept in maintainingpersonal hygiene and the environment. This research is a correlative research, the research design is using cross sectionalapproach, that is data taken in one time was done on Juli 2019 with total population 23santri as the sample which studied 23 santri and taken in total sampling. Data collectionthrough and tabulation then analyzed with statistical test kendall tau. Based on the test results on the Nonparametric Correlation table in the obtained rcount> r table. the conclusion is that H0 is accepted and H1 is rejected, meaning that there isno relationship between self-concept and the incidence of scabies at the Putri Al-QodiriIslamic Boarding School in Jember. Recommendations from the results of research to examinethe factors causing scabies.